Correlation between Interleukin-6 and Ferritin Serum in Pediatric Sepsis Patients - Wijayanti, Ida Ayu Agung; Gustawan, I Wayan; Karyana, I Putu Gede; Sidiartha, I Gusti Lanang; Gunawijaya, Eka; Mahalini, Dewi Sutriani; Widnyana, AANKP (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Sepsis is the leading cause of death in children. Sepsis is caused by dysregulation of immune system that triggers the production of pro-inflammatory cytokines, one of which is interleukin-6 (IL-6). In addition several markers of infection also increase such as c-reactive protein (CRP) and procalcitonin (PCT), moreover in sepsis serum ferritin also increase. Serum ferritin is secreted by stimulation of pro-inflammatory cytokines such as TNF-α, interleukin-1 (IL-1) and IL-6 that occur in the inflammatory process. AIM: to prove correlation between Interleukin-6 and ferritin serum in pediatric sepsis patient. METHOD: This was cross-sectional study. Subjects were children aged 1 month-18 years with sepsis in pediatric intensive care unit (PICU) and intermediate ward (IW) at Sanglah General Hospital Denpasar in period of September 2020 – June 2021. Statistical analysis was done by Pearson correlation test. RESULTS: Total 37 subjects were analyzed in this study. The median level of Interleukin-6 was 12 pg/ml (range, 1-355 pg/ml) and the median of ferritin level was 997 (range, 180-13418 ng/mL). The correlation between interleukin-6 and serum ferritin showed moderate positive correlation (r=0.54) which was statistically significant (p=0.001). After adjusting for the confounding variables, namely age, gender, nutritional status and time of sampling using partial correlation, the correlation between IL-6 and ferritin became strong with r=0.702 and p=0.00. CONCLUSION: There was a significant positive correlation after adjusting for the confounding variables between Interleukin-6 level and ferritin in pediatric sepsis patient.